(untitled) (Journal of Oriental Studies, 2016)
The order of words in the dictionary of al-Khalil ibn Ahmad, «Al Ain» in time to occupy an important position in the history of the formation of dictionaries. He created the first dictionary for centuries been used as an example - the following dictionaries were created on the basis of that dictionary. In this paper we will examine the methods of the system of words and give them descriptions.